EPILEPTIC SPASMS - K. Yu. Mukhin; M. B. Mironov (Русский журнал детской неврологии)
Epileptic spasms are epileptic seizures with sudden flexion/extension or of the mixed flexion and extension type, mainly involving the proximal and truncal muscles, that are normally longer than myoclonic seizures but shorter than tonic seizures, and last for about 1 second. For diagnostics of epileptic spasms, it is necessary that they are combined with ictal and interictal epileptiform patterns on electroencephalography (EEG). The first detailed clinical description of seizures of the infantile spasms type was provided by English pediatrician W.J. West in 1841. The term of infantile spasms is limited with age and means epileptic spasms that occur to children in early infancy, usually up to 1 y.o. Infantile spasms cannot be synonymous to the West syndrome. Infantile spasms are a type of epileptic seizures and West syndrome is a form of epilepsy that is usually manifested through hypsarrhythmia on the EEG and mental retardation, apart from infantile spasms. Epileptic spasms is the term broader than infantile spasms. Committee of the International League Against Epilepsy (ILAE) recommends exactly the “epileptic spasms” term, as this type of seizures is not a prerogative of the West syndrome and can be observed in children older than 1 y.o. and even in adults. The authors provided a detailed review of modern references devoted to epileptic spasms including the history of the issue, determination of the term, and position of epileptic spasms in modern classification systems, approaches to diagnostics including differential diagnosis, treatment, and prognosis.